Towards a Neuroscience of Mind-Wandering - Gruberger, Michal; Simon, Eti B.; Levkovitz, Yechiel; Zangen, Abraham; Hendler, Talma (Frontiers in Human Neuroscience, 2011)
Mind wandering is among the most robust and permanent expressions of human conscious awareness, classically regarded by philosophers, clinicians and scientists as a core element of an intact sense of self. Nevertheless, the scientific exploration of mind wandering poses unique challenges; mind wandering is by nature a spontaneous, off-task, internal mental process which is often unaware and usually difficult to control, document or replicate. Consequently, there is a lack of accepted modus operandi for exploring mind wandering in a laboratory setup, leading to a relatively small amount of studies regarding the neural basis of mind wandering. In order to facilitate scientific examination of mind wandering the current review categorizes recent literature into five suggested strategies. Each strategy represents a different methodology of mind wandering research within functional neuroimaging paradigms. Particular attention is paid to resting state brain activity and to the ‘default mode’ network. Since the default network is known to exert high activity levels during off-task conditions, it stands out as a compelling candidate in mind wandering research which in of itself is a rest based phenomenon. By summarizing the results within and across strategies we suggest further insights into the neural basis and adaptive value of mind wandering, a truly intriguing and unique human experience.